Introductory commentary: a strategic review of options for building on lessons learnt from IMCI and iCCM. (30th July 2018) - Jacobs, Marian; Merson, Michael
Abstract : Despite advances in child health over the past 20 years, children are still failing to reach their full health and development. Marian Jacobs and Michael Merson examine what the 2016 strategic review tells about how IMCI and iCCM have contributed to gains in child health, as well as the changes in child health epidemiology, health systems, technology and innovations, and health science